ANALISIS FENOMENA HIKIKOMORI DALAM DORAMA KAZOKU GAME - Intan Hapsari; Dina Dwi Astartia; Aldilah Alifany Darrienda; Angga Jalaludin Sidiq (Journal of Innovation Research and Knowledge, 2025)
This research is a cultural study that explores the causes and solutions for the issue of hikikomori as depicted in the drama Kazoku Gēmu. The aim of this study is to describe the causes and solutions for dealing with hikikomori issues. The method and technique used in this research are descriptive analysis with observation techniques. This study employs Freud's theories of anxiety and ego defense mechanisms. The findings indicate that the most common cause identified is neurotic anxiety, which includes the family’s lack of genuine concern, betrayal by friends, comparison to siblings, feelings of being unwanted, and lack of communication within the family. Additionally, five types of ego defense mechanisms are found in the drama: projection, reaction formation, displacement, rationalization, and compensation. As a solution to hikikomori issues, compensation is predominantly observed in forms such as resisting oppression, not avoiding problems, diligent studying, seeking satisfaction, and establishing communication with the family. In conclusion, the primary cause of hikikomori phenomena in Kazoku Gēmu is largely attributed to family-related issues. Therefore, hikikomori problems can be addressed within the family environment.